Karakteristik Kepemimpinan Pengurus dalam Membangun Loyalitas Anggota: Kasus pada Koperasi Mahasiswa Universitas Islam Bandung - Dindin Burhanudin; Talha Abdul Lakarim (LPPM Universitas Koperasi Indonesia, 2026)
Member loyalty is a key indicator of cooperative success because it reflects members' participation, utilization of cooperative services, and organizational sustainability. The Student Cooperative of Universitas Islam Bandung (KOPMA UNISBA) has experienced a decline in active membership and member participation despite continuous improvements in its business performance. This condition indicates a gap between the cooperative's financial achievements and its social performance in maintaining member loyalty. This study aimed to analyze the leadership characteristics of the cooperative board, identify the level of member loyalty, and formulate strategic efforts to strengthen loyalty through effective leadership practices. A descriptive quantitative approach was employed using a survey of active members of KOPMA UNISBA. Data were collected through questionnaires and analyzed using descriptive statistics based on Yukl's leadership theory and Bhuyan's cooperative member loyalty framework. The findings indicate that the board's leadership characteristics are generally categorized as moderately good, while member loyalty remains at a moderate level. Communication, program innovation, and opportunities for member participation were identified as the main aspects requiring improvement because they influence transactional, participatory, emotional, and ideological dimensions of member loyalty. The study concludes that participatory, communicative, adaptive, and value-based leadership strengthens members' sense of ownership, encourages active participation, and supports the long-term sustainability of student cooperatives. These findings contribute to the development of leadership practices in student cooperatives by emphasizing democratic governance and active member participation as fundamental cooperative principles.